Pre-ionization by AC Ohmic coil operation in the TST-2 spherical tokamak. (8th November 2017) - Ejiri, A.; Takase, Y.; Tsujii, N.; Togashi, H.; Furui, H.; Shinya, T.; Roidl, B.; Sonehara, M.; Yajima, S.; Yoshida, Y.; Yamazaki, H.; Kitayama, A.; et al.
Abstract: AC Ohmic coil operation experiments with frequencies up to 10 kHz were performed on the TST-2 spherical tokamak device, and the pre-ionization process was studied in detail. The minimum loop voltage for pre-ionization was 0.4 V, which corresponds to 0.5 V m − 1 at the inboard limiter. Dependences of growth rate and saturation level of the process on various parameters were obtained, and they are compared with a time-dependent 0-dimensional model based on Townsend avalanche and loss along field lines. Most of the dependences are reproduced qualitatively by the model, and quantitative differences are within a factor of several. However, the external vertical field dependence of the appearance time, which is defined as the time to observe a plasma, and the isotope effect cannot be reproduced by the model. An ambipolar diffusion state which is predicted theoretically but mitigated experimentally is discussed. It was found that secondary electron emission at the limiter surfaces is a candidate mechanism to mitigate the state.